Effects of replacing soybean meal with cottonseed meal in amino acid balanced diets on growth performance, apparent digestibility, ruminal fermentation, and microbial diversity in fattening Dorper × Hu crossbred sheep - Yue, Yuanrui; Lin, Jianwei; Lv, Gang; Liu, Baocang; Deng, Xiaoyu; Li, Yunjie; Li, Xiaobin; Chen, Kaixu (Frontiers in Veterinary Science, 2025)
Amino acid balanced cottonseed meal can effectively replace soybean meal in sheep diets, improving energy utilization without harming growth or health. This study aimed to investigate the effects of replacing soybean meal with cottonseed meal under amino acid balance on growth performance, blood biochemical indices, apparent digestibility, antioxidant function, and ruminal microbial diversity in fattening Dorper × Hu crossbred sheep. A total of 112 healthy 90-day-old Dorper × Hu crossbred rams with similar body weights were randomly divided into 4 groups with 28 sheep each, for a 63-day trial. The control group (CON) was fed a corn-soybean meal diet; T1 group replaced 50% soybean meal with cottonseed meal and balanced lysine and methionine; T2 group replaced 100% soybean meal with cottonseed meal and balanced lysine and methionine; T3 group replaced 100% soybean meal with degossypolized cottonseed meal and balanced lysine and methionine. Results showed no significant differences among groups in average daily gain, average daily dry matter intake, feed conversion ratio, blood biochemical indices, antioxidant indices, and ruminal microbial α and β diversity (p > 0.05). Cottonseed meal replacement significantly affected apparent digestibility, with T2 group exhibiting the highest digestibility of crude protein, crude fat, neutral detergent fiber, and acid detergent fiber (p < 0.05). Ruminal propionic acid concentration was significantly higher in replacement groups than in CON (p < 0.01), and acetic acid-to-propionic acid ratio was lower (p < 0.05). LEfSe analysis revealed the most microbial biomarkers enriched in T3 group. In conclusion, under amino acid balance, cottonseed meal can fully replace soybean meal without compromising growth and health while improving nutrient digestibility and rumen fermentation. These findings provide a scientific basis for soybean meal reduction strategies in ruminant feeding. Future research should explore optimal substitution strategies under different production systems and investigate long-term effects on meat quality and economic benefits.